Quality issue management and disclosure in forensic science: A survey of practice and perceptions. - Heavey, Anna L.; Houck, M. M.; Turbett, G. R.; Lewis, Simon (2025)
Addressing calls for transparency regarding errors and limitations in forensic processes is an ongoing concern for the forensic science service provider community and the stakeholders it serves worldwide. Foundational to this goal is developing a consistent approach to the identification of issues that have, or could have, an impact on the quality and reliability of forensic results. A standardized approach to the classification of quality issues detected within forensic agency management systems may be the strategic key to supporting consistent identification and disclosure, along with enhancing a positive quality culture throughout forensic service providers and building understanding of "error" in forensic science with end users of forensic information. A survey of international forensic science service providers was conducted to gain deeper insights into current systems of issue identification, classification, management, and disclosure along with perceptions on quality issues, their use and communication by forensic agency staff. The survey results demonstrate that development of a standardized approach would be of significant value to the forensic science community and its stakeholders, with potential benefit not only to improved communication and use of quality issue data but also in advancing a positive culture of quality and credibility in forensic service provision to support justice outcomes.